Peran Pelaku Konsumsi Islam dalam Membangun Ekonomi Islam di Era Digital - Ira Yulistin; Nayla Kamilatul Mukaromah; Rahmawati Rahmawati (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
The development of digital technology has revolutionized consumption patterns among consumers, including Muslim consumers. Digitalization has not only brought convenience and efficiency, but also created new challenges in the application of Islamic consumption values. Consumption, which is viewed as part of worship in Islamic economics, requires adherence to the principles of halal, thayyib, justice, prohibition of israf and gharar, and social responsibility. This study aims to conceptually examine how consumers play a role in strengthening the Islamic economy in the digital age, as well as how Sharia consumption principles can be ethically implemented in a dynamic digital environment. The method used is a literature review, examining various academic literature, scientific journals, and documents related to Islamic economics and the digitalization of consumption. The findings indicate that Muslim consumers hold a strategic position in shaping value-based markets, driving the growth of the halal sector, and supporting the sharia-compliant SME ecosystem. On the other hand, low sharia-based digital literacy and the dominance of digital consumerist culture pose challenges that must be anticipated. Strengthening literacy, adaptive regulations, and collective awareness transformation are needed to create a digital consumption pattern that is blessed, fair, and sustainable in accordance with the objectives of Islamic law.